Pola Kausalitas Nilai Tukar Rupiah Dan Ekspor Kopi Indonesia Ke Amerika Serikat - Dinda Retno Kinasih; Ladi Wajuba Perdini Fisabilillah (Universitas Negeri Surabaya, 2022)
One of the agricultural product that play a part in the business is coffee. The purpose ofthis research is to find out the causal relationship between the rupiah exchange rate andthe export of Indonesian coffee to the United States on 2000-2021. The quantitative methodis the method used by the researchers in this research. The analytical technique used is theGranger causality test. In the results of this research, one-way causality was obtained onthe coffee export variable affecting the rupiah exchange rate but an inverse causality wasnot found in the rupiah exchange rate variable on coffee exports.Keywords: Coffee, Exports, Exchange Rate, Granger Causality